Aesthetics and politics in the combat (dite de combat) cinema:: the films of Ousmane Sèmbene between reality and fiction in the competition for memory - dos Santos Alves, Nathan (O Mosaico, 2024)
Sembène’s cinema is mostly studied from the perspective of his activism and his role as a pioneer of African cinemas. Given the importance and celebration of this filmmaker's centenary in 2023, seeking to work on the audiovisual production of this memorable Senegalese filmmaker, this article approaches the aesthetic aspects in his political way of filming, showing how his politics are structured aesthetically as to Frantz Fanon’s dite de combat, or the awakening of the people through culture. Applying two methodological approaches, filmmakers and their works are taken as objects of study and possibility of theoretical elaboration, through the theory of filmmakers (Penafria, Santos & Piccini, 2015; Graça, Baggio & Penafria, 2020), and also in terms of a discursive analysis as a film study, keeping in mind the importance of going beyond films and artists, as proposed by Robert Stam and Ella Shohat (2006). We explored several films by Sembène: La Noire de... (1966), Emitai (1971), Xala (1975) and Ceddo (1997), aiming to understand the aspects that permeate all the works, not only the regularities, but also the deviations and aesthetic-political specificities of each one.